Continuous Inking Affects the Biological and Biochemical Responses of Cuttlefish Sepia pharaonis - Jiang, Maowang; Zhao, Chenxi; Yan, Runxuan; Li, Jianping; Song, Weiwei; Peng, Ruibing; Han, Qingxi; Jiang, Xiamin (Frontiers in Physiology, 2019)
Several marine mollusks, including cephalopods (cuttlefish, squid, and octopus) and gastropods (e.g., sea hares), can release a colored ink secretion when chased by predators or stimulated. Ink release is part of a defensive response but the threshold for the biochemical responses caused by stimulation is unknown. The present study aimed to reveal anti-predator responses of cuttlefish, such as escaping via inking and/or jetting, and to investigate its biological and biochemical responses to continuous ink release. Results showed that the behavioral responses to continuous ink release mainly manifested as blazing body pattern changes. Cuttlefish escaped from predators covered by jetting/inking and warned the potential threats by displaying a unique body pattern. Moreover, persistent inking in the presence of an overt stimulus caused uncontrollable ink release from the ink duct/anal canal (loss of control). This study first verified the characteristics of the cuttlefish ink solution, prepared a standard curve of ink solution concentrations, and fitted the relationship function between the release frequency and the released ink weight. Biological statistics indicated that cuttlefish has the ability to continuously release ink (releasing approximately 90% of the ink from the ink sac), and that the individuals adapted well during the recovery period. However, re-releasing ink would result in “over-exploitation” and high mortality. Hexokinase (HK), pyruvate kinase (PK), and superoxide dismutase (SOD) activities, as well as malondialdehyde (MDA) concentration increased or remained stable in different tissues after releasing ink. The expression of heat shock protein 90 (HSP90) and arginine kinase (AK) were upregulated by stimuli in all tissues. Biochemical changes indicated that continuous inking not only consumed considerable energy but also damaged the tissues. In summary, cuttlefish released almost 90% of their ink for active defense against predators, and it took about 30 d for the ink sac to be refilled, but “over-exploitation” resulted in serious physiological damage. These findings will be helpful to further study the defense and ink release mechanisms, and to consider animal health and welfare when using cephalopods as experimental animals and for aquaculture practices.